Prevalence of hypertension and obesity among non-academic staff in a Nigerian University : Hypertension and Obesity among Nigerian Staff - Akinpelu Temitope O; Gbenga Oladosu; Olajide Bolanle R; Oladeji Oluwatoyin E; Adebowale Agboola A; Onabanjo Oluseye O (Indonesian Nutrition Association, 2023)
Background: The aim of achieving a healthy society has motivated and led many researchers to understand the prevalence of diseases to create awareness and assess interventionsâ€™ effectiveness. Objective: This study determines the prevalence of hypertension and obesity among the non-academic staff of the Federal University of Agriculture, Abeokuta. Methods: The study design was descriptive and cross-sectional. 300 Non-academic staff of the institution were randomly selected and data were obtained on their sociodemographic and socioeconomic characteristics, predisposing risk factors of hypertension, anthropometry, and blood pressure measurements using a structured self-administered questionnaire and standard procedures. Data were analyzed and presented using descriptive and inferential statistics. Statistical significance was established at p<0.05. Results: The mean age was 42Â±8.0years, there were more female respondents (56.0%) than male respondents (44.0%) and 76.0% of the respondents were married. Results further revealed a high prevalence of overweight and obesity (52%), pre-hypertension and hypertension (40%), and risk of abdominal obesity (84%). Conclusion: Non-academic staff are an essential component of the workforce and workplace intervention is essential to reduce the work nature risk factor of Obesity and Hypertension to prolong lives, and boost productivity and economic growth.